Perkembangan Tari Marcok Di Sanggar Seni Ilok Rupo Kota Sungai Penuh Provinsi Jambi - Inessya Lelioritha NS; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2021)
The research aims to reveal, describe, and analyze the development of Marcok Dance at Ilok Rupo Art Studio, Sungai Penuh City. This research belongs to a qualitative research using a descriptive analysis method. The types of data in this study were primary and secondary data. The main instrument was the researcher itself, and it was assisted by supporting instruments such as writing tools and cameras. The data were collected through literature, observation, interviews, and documentation. The data analysis was done through data collection, data reduction, data presentation, and conclusions drawing. The results show that the traditional Marcok Dance had developed into a creation Marcok Dance. This development can be seen from the management of movements, dancers, floor patterns, accompaniment music, clothing, time performance, and place of performance. In motion, there are 2 new motion additions. Related to the floor pattern, there is a reduction from 26 to 14 creation Marcok dance floor patterns. Costumes have developed in terms of accessories used. In addition, there is an additional musical instrument called gong. The development process of Marcok Dance at the Ilok Rupo Art Studio, Sungai Penuh City is supported because of the desire of Ilok Rupo Art Studio to keep the traditional Marcok Dance by develop it so it is attractive for the community to use. Moreover it is useful as a forum for young people to learn how to maintain cultural heritage, and it becomes an identity in the local area.